2005
DOI: 10.1177/1471301205055028
|View full text |Cite
|
Sign up to set email alerts
|

Group home care for adults with intellectual disabilities and Alzheimer’s disease

Abstract: The growing numbers of individuals with intellectual disabilities affected by Alzheimer's disease and related dementias has raised new challenges for community care providers. This article examines means of providing community group home-based care in a sample of care providers in five different countries. The aim is to identify trends that have emerged. Two samples of group homes for adults with intellectual disabilities affected by dementia were studied to determine: (1) what are the physical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 22 publications
1
59
1
Order By: Relevance
“…Further, the fact that most of the carers opted in the future for some kind of small family-living situations for their offspring, over institutional care, is telling. This reinforces the belief that either other family members may provide aid as caregiving becomes problematic or that these carers may turn to agencies that are operating and promoting alternative care settings, primarily small neighborhoodbased group homes (Janicki et al, 2005).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Further, the fact that most of the carers opted in the future for some kind of small family-living situations for their offspring, over institutional care, is telling. This reinforces the belief that either other family members may provide aid as caregiving becomes problematic or that these carers may turn to agencies that are operating and promoting alternative care settings, primarily small neighborhoodbased group homes (Janicki et al, 2005).…”
Section: Discussionmentioning
confidence: 79%
“…It was noteworthy that the types of initial changes noted by these carers paralleled for the most part those noticed by paid formal carers in group homes (Janicki et al, 2005). Primarily early stage changes observed involved noted forgetfulness, losses in personal skills, and changes in personality, all behaviors also noted by both group home staff in our previous study and generally reported in the literature (Donaldson et al, 1998;Janicki et al, 2005). Noteworthy also was the fact that the more challenging behaviors, such as wandering, becoming argumentative or aggressive, experiencing sleeping difficulties, incontinence, and rummaging -generally indicative of mid-stage dementia -were also present and commented upon by both staff and the family carers.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…At mid-stage supervising eating and drinking, and behaviour support took longer, whereas at end-stage assisting people to use the toilet, and health-related care took longest . Similarly, Janicki et al (2005) , 2002) found that staff did not spend extra time caring for individuals who were in early stage dementia (n ¼ 9) compared to those without dementia (n ¼ 11). While the nature of caregiving tasks was not reported to be difficult using the Caregiver Difficulty Survey-Intellectual Disability , seven of the nine carers working with individuals with early stage dementia experienced stress on the Maslach Burnout Inventory (Maslach et al, 1996).…”
Section: Staff Training In Dementiamentioning
confidence: 93%
“…There is a growing literature on the accommodation needs of people with LD and dementia, much of which recommends 'ageing in place' -avoiding moves by keeping people in their familiar home environment with additional support (Janicki et al, 2005). Kerr (1997) has described the detrimental effects on people with dementia of multiple moves.…”
Section: Clinical Developmentsmentioning
confidence: 98%